Unravelling the role of rhizospheric plant-microbe synergy in phytoremediation: A genomic perspective - Agarwal P.; Giri B.S.; Rani R. (My University, 2025)
Background: Accretion of organic and inorganic contaminants in soil interferes in the food chain, thereby posing a serious threat to the ecosystem and adversely affecting crop productivity and human life. Both endophytic and rhizospheric microbial communities are responsible for the biodegradation of toxic organic compounds and have the capability to enhance the uptake of heavy metals by plants via phytoremediation approaches. The diverse set of metabolic genes encoding for the production of biosurfactants and biofilms, specific enzymes for degrading plant polymers, modification of cell surface hydrophobicity and various detoxification pathways for the organic pollutants, plays a significant role in bacterial driven bioremediation. Various genetic engineering approaches have been demonstrated to modulate the activity of specific microbial species in order to enhance their detoxification potential. Certain rhizospheric bacterial communities are genetically modified to produce specific enzymes that play a role in degrading toxic pollutants. Few studies suggest that the overexpression of extracellular enzymes secreted by plant, fungi or rhizospheric microbes can improve the degradation of specific organic pollutants in the soil. Plants and microbes dwell synergistically, where microbes draw benefit by nutrient acquisition from root exudates whereas they assist in plant growth and survival by producing certain plant growth promoting metabolites, nitrogen fixation, phosphate solubilization, auxin production, siderophore production, and inhibition or suppression of plant pathogens. Thus, the plant-microbe interaction establishes the foundation of the soil nutrient cycle as well as decreases soil toxicity by the removal of harmful pollutants. Conclusion: The perspective of integrating genetic approach with bioremediation is crucial to evaluate connexions among microbial communities, plant communities and ecosystem processes with a focus on improving phytoremediation of contaminated sites. © 2020 Bentham Science Publishers.